How Malaysian primary ESL learners build vocabulary using multimedia technology - Nur Sakinah binti Ahmad Nasaruddin (Kulliyyah of Education, International Islamic University Malaysia, 2018)
English language is important in Malaysia but many students are still poor in English vocabulary. Learning using multimedia technology can be an alternative to help them to learn English vocabulary. Hence, this research intends to study the process of how Malaysian primary ESL learners build English vocabulary using multimedia technology. The types of multimedia technology tools chosen by the students and the reasons why they chose the tools in learning vocabulary were also investigated. This study used a qualitative approach by conducting semi-structured interviews with three primary school students aged 12 years old from Sekolah Kebangsaan Desa Setapak. It was found that the students chose three main types of multimedia tools which are audio, audio-visual and video games. The reasons why they prefer to use the multimedia tools in building English vocabulary are a positive feeling that the tools provide, multi-tasking features of the tools and advantages of the multimedia tools. The process of learning new words using multimedia tools is organised into four stages: First encounter - Being curious to find out- Finding out - Remembering. The findings suggest English teachers to include multimedia tools in teaching because it is convenient for the students to build vocabulary as the words are learned in context and enhanced with visuals.